Optimalisasi Pendidikan Kecakapan Hidup (Life Skill) melalui Mata Pelajaran Geografi di SMA - Mochamad Enoh (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2007)
Quality teachers, definitely required by competency-based curriculum (CBC), are expected to equip students with life skills to optimize their potentials. Geography teachers are also expected to do so, since Geography is one of the subjects that enables life skills to develop in order that students can learn how to deal with life problems. Through CBC, Geography teachers can train students in life-skill development, resulting in more quality human resources. Though unable to solve all the existing problems, better quality teachers contribute to the improvement of human resources.